2012
DOI: 10.4067/s0718-16202012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of control strategies for decision-making regarding Digitaria sanguinalis in glyphosate-resistant soybeans

Abstract: Cien. Inv. Agr. 39(2): 299-308. A bioeconomic model was developed for decision-making regarding large crabgrass (Digitaria sanguinalis) control in glyphosate-resistant soybeans in the Rolling Pampas of Argentina. The model was used to evaluate the economic returns of four different glyphosate-based strategies for weed control. In the absence of herbicide application (T1), the soil seed bank increases to an equilibrium density of 12,079 seeds m -2 in three years. A single herbicide application during the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Considering that glyphosate is the main agronomic tool used to control D. sanguinalis under no‐tillage systems in glyphosate‐tolerant soybean and corn crops, 8 glyphosate resistance evolution in D. sanguinalis emerges as a challenge for farmers in the Rolling Pampas agricultural region. Nevertheless, other herbicides have been shown to be effective in controlling Dgs R plants in different crops, as no evidence of multiple herbicide resistance was found (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that glyphosate is the main agronomic tool used to control D. sanguinalis under no‐tillage systems in glyphosate‐tolerant soybean and corn crops, 8 glyphosate resistance evolution in D. sanguinalis emerges as a challenge for farmers in the Rolling Pampas agricultural region. Nevertheless, other herbicides have been shown to be effective in controlling Dgs R plants in different crops, as no evidence of multiple herbicide resistance was found (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In extensive cropping areas from Argentina, D. sanguinalis is one of the most common weeds of soybean, sunflower, maize and sorghum crops and is likewise well adapted to both cultivated and no‐tillage systems 2,6,7 . This species shows an extended period of seedling emergence with several overlapping cohorts during spring and summer, and a high vegetative growth rate and fecundity 8,9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported different survival rates between cohorts. For instance, C. bonariensis, survival rate ranges from 0.44 to 0.13; Salsoa australis from 0.75 to 0 and Digitaria sanguinalis from 0.2 to 0.003 (Borger, et al, 2009;Oreja et al, 2012;Zambrano-Navea et al, 2018). The difference in survival can be explained by the different establishment times.…”
Section: Seedling Emergence Patternmentioning
confidence: 99%
“…(large crabgrass) is a troublesome annual weed present in most summer crops around the world (Mohler & Callaway, 1995;Monks & Schulteis, 1998;Sarker et al, 2002;Aguyoh & Masiunas, 2003;Bhowmik, 2003;Fu & Ashley, 2006). In Argentinean soyabean fields, high densities of this weed can cause high yield losses (above 90%; Oreja et al, 2012). Despite the good chemical control that can be obtained with glyphosate (around 98%;Culpepper et al, 2001;Van Gessel et al, 2001;Norsworthy, 2004), over the last 20 years, this species has shown very high constancy values in the Argentinean Pampas (Puricelli & Tuesca, 2005;de la Fuente et al, 2006;Scursoni & Satorre, 2010).…”
Section: Introductionmentioning
confidence: 99%